The Influence of Corporate Governance and Culture on Corporate Reputation - Choiriah, Siti; Augustine, Yvonne; Basri, Yuzwar Z.; Khomsiyah, Khomsiyah (Technium Social Sciences Journal, 2021)
This research aims to determine the effect of corporate governance and culture on the company’s reputation. The population in the research is industrial companies in Indonesia, the research sample of managers who are directly related to corporate governance, culture, and corporate reputation. Data collection uses survey data sent via Google Form and email. A total of 178 interviewees were analyzed using SEM PLS and it was found that corporate governance and culture affect company reputation. The policy implication of this research is to urge companies in Indonesia to implement good corporate governance because the implementation of GCG in Indonesia tends to lag behind other ASEAN countries, it also pays attention to policymakers about the protection of minority shareholders and develops a governance framework. manage companies that do not hinder the development of active equity markets.